Greene’s Quest for Seediness in Journey Without Maps - Upadhyay, Toya Nath (Dhaulagiri Journal of Contemporary Issues, 2023)
This paper examines Graham Greene’s travel text, Journey Without Maps (1936/2010), so as to discover why Greene makes a quest for seediness, especially a primitive one. The study is drawn by Greene’s paradoxical fascination to the seediness, which literally suggests the squalor or ugliness. But why does he like it? This is the major concern of the study. Using the concept, primitivism, that was frequently used by the Western travel writers to depict the non-Western peoples and their societies during the colonial era, the study analyzes and interprets the text, and claims that Greene’s journey to the interior of Liberia is the journey of his escape from the contemporary seediness of civilization that he experiences in Britain into the seediness of primitivism that he supposes to find in Liberia where the civilization has comparatively a weaker grip upon human being. After the textual analysis, the study expects to add a new perspective to the critical reading of the Western texts written about the non-Western societies representing them as the primitive and uncivilized others.